Metformin and propranolol combination prevents cancer progression and metastasis in different breast cancer models - Rico, María José (2016)
Fil: Fil: Rico, María José. Institute of Experimental Genetics. School of Medical Sciences. National University of Rosario; Rosario; Argentina